Mettre en dessins le travail scientifique - Claire Marc; Verena Richardier (Images du Travail, Travail des Images)
This article deals with the work of imaging scientific articles in sociology and in life and earth sciences. One of the authors is a sociologist, the other is an oceanographer and scientific mediator. They have faced both enthusiastic and critical reactions from the scientists whose research they have illustrated. They offer a reflection based on their respective experiences. From a transdisciplinary perspective, they reflect on how the comic strip has become a hybrid object, between drawing and science. As tools for transmission, but also as food for thought, drawing echoes multiple issues that resonate across sciences. We propose an article accompanied by its drawn version to reflect on those issues.